PENERAPAN METODE TEAM QUIZ DALAM PEMBELAJARAN TEMATIK INTEGRATIF UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA KELAS 1 SDN CIDOKOM 01 RUMPIN BOGOR - Elsa maryana (JURNAL ILMIAH PENELITIAN MAHASISWA, 2024)
This study aims to analyze the impact of the Team Quiz method on students’ motivation and learning activity in integrative thematic learning at SDN Cidokom 01 Rumpin, Bogor. The research subjects were 29 first-grade students who initially showed low learning motivation. This action research was conducted in two cycles, each consisting of planning, action, observation, and reflection. The observation results indicated that the implementation of the Team Quiz method significantly improved students’ learning motivation. In the first cycle, although there was an increase in student activity, the results did not meet the success criteria. However, improvements made in the second cycle led to more optimal outcomes, with an average student activity rate reaching 85.36% in the second meeting of cycle II. The motivation scale results also showed an improvement, with 90% of students in cycle II categorized as having high motivation. This study concludes that the Team Quiz method is effective in enhancing students’ motivation and learning activity, as evidenced by significant improvements in each cycle. However, challenges remain in ensuring that all students receive equal attention.